Prawo rolne w rosyjskim systemie prawnym: stanowienie, rozwój i tendencje - Akmanov, Stiepan Stiepanovicz (Wydawnictwo Naukowe UAM, 2011)
The rapid development of agricultural law as a new branch in the Russian legal system is determined both by the radical transformation of the social and political system in Russia and the creation of new legal foundations for the activity of agricultural producers. This law, due to the characteristics and structure, is defined as a complex specialised branch of law, which forms a comprehensive system of related legal norms regulating agricultural social relations in the sphere of economic activity. Agricultural relations are of considerable social importance, which results in a situation when they become the subject of an independent, separate legal regulation, a special set of different integrated norms and legal institutions. At present the Russian agricultural law has its own legal foundations, which are characterised by a sufficiently broad scope and cover different aspects of activity of agricultural producers under market economy conditions. Legal institutions in agricultural law are unique in cha-racter not only due to their subject, but also the contents of objectives of legal regulations. In view of the rapid development of agrarian relations the author defines trends and prospects for further development of agricultural law in Russia as an independent branch within the Russian legal system.

Il rapido sviluppo del diritto agrario in quanto nuova branca nel sistema giuridico russo è determinato sia dalla radicale trasformazione del sistema socio-politico della Russia sia dalla creazione di nuove basi legali dell’attività dei produttori agricoli. Questo diritto, viste le caratteristiche e la struttura, viene descritto come branca specializzata e comp¬lessa della legge, la quale crea un sistema coerente di norme giuridiche interconnesse che disciplinano i rapporti agricoli sociali nella sfera di attività economica. I rapporti agricoli hanno una notevole importanza sociale, il che fa sì che essi diventino oggetto di una indi-pendente, separata regolazione giuridica, un insieme speciale di una serie integrata di sva-riate norme e istituzioni giuridiche. Il diritto agrario russo possiede ormai una sua propria base giuridica, caratterizzata da un ambito sufficientemente ampio, la quale com-prende diversi aspetti dell’attività dei produttori agricoli nelle condizioni di economia di mercato. Le istituzioni giuridiche del diritto agrario hanno una loro specificità non solo in base al soggetto, ma anche al contenuto e agli obiettivi della regolazione giuridica. Dato il rapido sviluppo dei rapporti agrari, l’Autore definisce le tendenze e le prospettive di un ulteriore sviluppo del diritto agrario in Russia come ramo indipendente nel sistema giuridico russo.